Holocene floristic diversity and richness in northeast Norway revealed by sedimentary ancient DNA (sedaDNA) and pollen - Clarke, Charlotte; Edwards, Mary Elizabeth; Brown, Antony Gavin; Gielly, Ludovic; Lammers, Youri; Heintzman, Peter D.; Murguzur, Francisco Javier Ancin; Bråthen, Kari Anne; Goslar, Tomasz; Alsos, Inger Greve (Boreas, 2018)
Source at https://doi.org/10.1111/bor.12357 We present a Holocene record of floristic diversity and environmental change for the central Varanger Peninsula, Finnmark, based on ancient DNA extracted from the sediments of a small lake ( sed aDNA). The record covers the period c. 10 700 to 3300 cal. a BP and is complemented by pollen data. Measures of species richness, sample evenness and beta diversity were calculated based on sed aDNA sampling intervals and 1000‐year time windows. We identified 101 vascular plant and 17 bryophyte taxa, a high proportion (86%) of which are still growing within the region today. The high species richness (>60 taxa) observed in the Early Holocene, including representatives from all important plant functional groups, shows that modern shrub‐tundra communities, and much of their species complement, were in place as early as c. 10 700 cal. a BP. We infer that postglacial colonization of the area occurred prior to the full Holocene, during the Pleistocene‐Holocene transition, Younger Dryas stadial or earlier. Abundant DNA of the extra‐limital aquatic plant Callitriche hermaphroditica suggests it expanded its range northward between c. 10 200 and 9600 cal. a BP, when summers were warmer than present. High values of Pinus DNA occur throughout the record, but we cannot say with certainty if they represent prior local presence; however, pollen influx values >500 grains cm −2 a −1 between c. 8000 and 7300 cal. a BP strongly suggest the presence of pine woodland during this period. As the site lies beyond the modern tree limit of pine, it is likely that this expansion also reflects a response to warmer Early Holocene summers.